2022
DOI: 10.3389/fpsyt.2022.874090
|View full text |Cite
|
Sign up to set email alerts
|

Connectivity-Based Brain Network Supports Restricted and Repetitive Behaviors in Autism Spectrum Disorder Across Development

Abstract: IntroductionAutism spectrum disorder (ASD) is a lifelong condition. Autistic symptoms can persist into adulthood. Studies have reported that autistic symptoms generally improved in adulthood, especially restricted and repetitive behaviors and interests (RRBIs). We explored brain networks that are related to differences in RRBIs in individuals with ASDs among different ages.MethodsWe enrolled 147 ASD patients from the Autism Brain Imaging Data Exchange II (ABIDEII) database. The participants were divided into f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 49 publications
0
1
0
Order By: Relevance
“…Most of the significant results were observed in adaptive/cognition behaviors. Previous studies have shown that genetic influences on language, social communication, restricted/repetitive behaviors, and the symptoms can decrease with age ( 46 , 47 ). We speculated that environmental factors play an important role in social communication and restricted/repetitive behaviors, resulting in a reduced effect of genetic risk on these ASD core phenotypes.…”
Section: Discussionmentioning
confidence: 99%
“…Most of the significant results were observed in adaptive/cognition behaviors. Previous studies have shown that genetic influences on language, social communication, restricted/repetitive behaviors, and the symptoms can decrease with age ( 46 , 47 ). We speculated that environmental factors play an important role in social communication and restricted/repetitive behaviors, resulting in a reduced effect of genetic risk on these ASD core phenotypes.…”
Section: Discussionmentioning
confidence: 99%